Work Environment Factors and Retaliations Against Whistleblowing Intention - Vallentino Dante Mulyono; Martdian Ratna Sari (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
The Whistleblowing is a powerful tool for detecting fraud. However, according to the 2024 Corruption Perception Index, Indonesia’s score has declined significantly compared to previous years, showing no signs of a full recovery. This, suggesting a weak intention to whistleblow in Indonesia. This study aims to identify factors contributing to this weakness using the Partial Least Squares (PLS) method. The research considers both intrinsic and extrinsic factors, represented by rationalization, fear of retaliation, reward/punishment systems, work environment, and internal system responsiveness. The findings reveal that fear of reprisals, the work environment, and internal system responsiveness significantly influence whistleblowing intention.